Bones. The complete ninth season [videorecording (DVD)] - Hanson, Hart (2014)
TV's most anticipated wedding day has arrived! And since dealing with death is part of their jobs, it probably won't part FBI Special Agent Seeley Booth and quirky forensic anthropologist Temperance Brennan, aka Bones. But Bones and Booth must still address a serial killer's threat to murder five people if the couple marries. Meanwhile, they work to solve murder mysteries as they devote themselves to each other and their young daughter.